PENGEMBANGAN PERKEBUNAN KARET DALAM USAHA PENINGKATAN EKONOMI DAERAH DAN PENDAPATAN PETANI DI PROVINSI ACEH - Kasman, Kasman (Universitas Muhammdaiyah Surakarta, 2009)
The governmentâs effort to reduce the number of unemployment and poverty in ac- cordance with the Medium Term Development Plan amounted 5,1 percent is difficult to achieve if there is no effort to develop the Rill Sector. The revitalization of Rubber Plantation is based upon: (1) has a strategic role as a source of public revenue, (2) both domestic and export markets, (3) able to absorb labor, (4) ensuring environmental sustainability. The obstacles faced by the Rubber development focus on: (1) Productivity of the plantation is low, because there are many plantation which are damage by wild plant material, (2) the domestic downstream industry is less developed, (3) there is no special funding available for plantations, and (4) the policies are less supportive the development of plantation. Based on the development of rubber in 1992-1996, the result has been able to encourage economic growth and to increase the farmerâs incomes in Aceh significantly.